Thermal Performance Improvement of a Counter-Flow Double-Pipe Heat Exchanger Using a Twisted Turbulator - Eric Maspaitella; Nicolas Titahelu; Cendy Sophia Edwina Tupamahu (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Internal combustion systems, such as 5 KVA generators, convert only part of fossil fuel energy into useful work, while the remaining energy is released as waste heat through exhaust gas, cooling systems, and mechanical losses. This study aims to improve the thermal performance of a double-pipe heat exchanger using a twisted turbulator by varying the pitch-to-diameter ratio, p/d, from 0.8 to 3.9. The experiment was conducted at the Thermodynamics and Heat Transfer Laboratory, Faculty of Engineering, Pattimura University, using five p/d variations, namely 0.8, 1.6, 2.4, 3.2, and 3.9. The operating conditions were maintained constant, with a hot fluid inlet temperature of 523.2 K, a cold fluid inlet temperature of 308.2 K, a cold fluid velocity of 1.0 m/s, and a hot fluid velocity of 5.0 m/s. The main components included a copper tube bank, steel pipe casing, thermocouples, flowmeter, pipe system, and valves. The performance parameters were evaluated using Reynolds number, Prandtl number, friction factor, Nusselt number, overall heat transfer coefficient, actual heat transfer rate, maximum heat transfer rate, and effectiveness. The results show that the best performance was obtained at p/d = 0.8, producing a cold fluid outlet temperature of 425.84 K, Nusselt number of 7.569, overall heat transfer coefficient of 0.2029 W/m²·K, and effectiveness of 39.95%. The lower p/d ratio enhanced swirl flow, turbulence intensity, fluid mixing, and thermal boundary layer disruption. Therefore, p/d = 0.8 is recommended for improving the tested heat exchanger performance in small-scale waste heat recovery applications under laboratory operating conditions and design.